The complete mitochondrial genome of Lucilia shenyangensis (Diptera: Calliphoridae) - Chen, Tingjun; Li, Xiangrong; Wang, Yong (Mitochondrial DNA. Part B. Resources, 2021)
Lucilia shenyangensis Fan, 1965 (Diptera: Calliphoridae) is of potential importance in epidemiology, veterinary medicine, and forensic entomology due to their necrophilous habit and behaviors associated with mammals. In this study, we report the complete mitochondrial genome (mitogenome) of L. shenyangensis. The mitogenome is 14,989 bp in length, comprising 13 protein-coding genes (PCGs), two ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and a non-coding control region. The arrangement of genes is identical to that of the ancestral metazoan. Nucleotide composition revealed a high A/T bias, accounting for 76.50% total mitogenome nucleotides (A 39.2%, G 9.6%, C 14.0%, T 37.3%). Phylogenetic analysis indicated that L. shenyangensis was clear separated from other blow flies and emerged as the sister lineage to the rest species from genus Lucilia (L. illustris, L. sericata, L. coeruleiviridis, and L. porphyrina). The mitogenome data of L. shenyangensis could facilitate further evolutionary genetic researches on blow flies.